2020
DOI: 10.3389/fpsyg.2020.607233
|View full text |Cite
|
Sign up to set email alerts
|

The Rebooting in Sports and Physical Activities After COVID-19 Italian Lockdown: An Exploratory Study

Abstract: The lockdown imposed in Italy to reduce the spread of COVID-19 posited unusual challenges to people practicing sports and physical activities. The rebooting of activities highlighted the need to cope with new behaviors and routines, such as wearing a face mask while exercising. We conducted a web-based survey in Italy at the start of physical activities’ rebooting, to investigate how people reacted to the new norms. Participants completed the questionnaires assessing insomnia, regulatory self-efficacy, optimis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…At the same time, vigor, a positive factor, increased its value in relation to weeks 1 and 6. This trend towards improvement in mood behavior is shared by the study of Mehrsafar et al [24], carried out in Iranian participants, and the study of Guicciardi and Pazzona [25], carried out in a sample of the Italian population. Furthermore, they point out that understanding the psychological implications of the restart phase can help to adopt appropriate behaviors for practicing sports in the COVID-19 situation.…”
Section: Discussionmentioning
confidence: 79%
“…At the same time, vigor, a positive factor, increased its value in relation to weeks 1 and 6. This trend towards improvement in mood behavior is shared by the study of Mehrsafar et al [24], carried out in Iranian participants, and the study of Guicciardi and Pazzona [25], carried out in a sample of the Italian population. Furthermore, they point out that understanding the psychological implications of the restart phase can help to adopt appropriate behaviors for practicing sports in the COVID-19 situation.…”
Section: Discussionmentioning
confidence: 79%
“…Although regular physical activity is essential for public health and mental well-being, many questions arose during the COVID-19 crisis concerning the risks of fitness-related activities in public areas and indoor sports facilities, mainly due to the perceived and actual infection risk. Guicciardi et al proposed that fear of possible infection in indoor areas was the main reason for changed sports behavior in indoor facilities [ 30 ]. However, national customs along with governmental restrictions and lockdowns might impact sports behavior even more radically, arguing for an evaluation of national public perceptions not ultimately transferrable to other settings.…”
Section: Discussionmentioning
confidence: 99%
“…The current virus outbreak has forced us to think about the risks of future pandemics or other global crises, and how we may increase our resilience to withstand their short-, medium- and longer-term impacts in all areas of social life. Lockdowns, social distancing, self-isolation, quarantine, home schooling, teleshopping, and teleworking during a pandemic contradict an active lifestyle, and are likely to contribute to physical inactivity [ 10 , 12 , 14 , 18 , 19 , 21 , 30 , 36 , 41 ], and subsequently in lower life satisfaction [ 19 , 20 ]. Combining the need for novel routines in active living in view of closed fitness facilities with a new awareness for the value of urban and rural green areas, life satisfaction could be eventually restored to a pre-pandemic level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 6 August 2021, normal activities gradually returned, especially for vaccinated persons with a green pass [4]. The reactivation of activities showed the necessity to deal with new routines and habits [5]. Some studies have shown favorable changes in individuals' eating habits, with an increase in the number of meals prepared and consumed at home [3][4][5].…”
Section: Introductionmentioning
confidence: 99%